All Days 1994
DOI: 10.2118/28050-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of borehole breakouts from laboratory and field tests

Abstract: Laboratory testing of granite blocks containing a circular borehole was carried out with uniaxial and biaxial loading conditions, and with borehole diameters ranging from 5 to 103 mm. Borehole breakouts were also investigated in situ using borehole diameters ranging from 75 to 3500 mm. Results show that the same strength-scaling law cannot be applied to both laboratory and in situ breakouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…As pointed out by Martin et al (1994), the scale effect is important for borehole diameters smaller than 75 mm. Comparing laboratory and borehole breakout data in the field Martin et al (1994) found different scaling laws. In this case study, Lac du Bonnet granite from the underground research laboratory URL in Canada was investigated.…”
Section: Stress State-scale Relationsmentioning
confidence: 94%
See 1 more Smart Citation
“…As pointed out by Martin et al (1994), the scale effect is important for borehole diameters smaller than 75 mm. Comparing laboratory and borehole breakout data in the field Martin et al (1994) found different scaling laws. In this case study, Lac du Bonnet granite from the underground research laboratory URL in Canada was investigated.…”
Section: Stress State-scale Relationsmentioning
confidence: 94%
“…The extrapolation from laboratory to field conditions, however, is difficult due to an apparent increase in rock strength around smaller diameter boreholes. The strength-scale dependence seems to disappear for boreholes with diameters larger than about 75 mm (Martin et al 1994). Physical aspects of breakout micro-failure mechanisms were recently reviewed by Haimson (2007).…”
Section: Borehole Breakoutsmentioning
confidence: 99%
“…In conjunction with the MBE, borehole breakouts were studied extensively in situ at the URL [15]. In a series of boreholes with diameters ranging from 150 to 1240 mm, observed borehole breakouts did not form diametrically opposite one another.…”
Section: Borehole Breakout Studiesmentioning
confidence: 99%
“…This phenomenon is typical for hard crystalline rocks such as granite under compression with no or small lateral confinement (see e.g. Cook, 1990a and1990b;Lee and Haimson, 1993, Martin et al, 1994, Haimson and Lee, 1995, Amadei and Stephansson, 1997. In the case of shear fracturing, shear failure along one or more shear bands extends from the borehole wall into the rock.…”
Section: Introductionmentioning
confidence: 90%